Phenanthrenes/dihydrophenanthrenes: the selectivity controlled by different benzynes and allenes. Issue 96 (20th November 2020) - Yao, Liangliang; Fang, Bo; Hu, Qiong; Lei, Yu; Bao, Li; Hu, Yimin
Abstract : A method for the intermolecular annulation of benzynes with allenes is disclosed. Abstract : A method for the intermolecular annulation of benzynes with allenes is disclosed. This protocol utilized allenes as an unconventional diene component for the selective synthesis of phenanthrenes and dihydrophenanthrenes under the control of different benzyne precursors, featuring high atom-economy and good functional group compatibility. Density functional theory (DFT) calculations reveal that different migratory routes of the aromatic C–H bond are crucial for the observed selectivity.